Amplitude analysis of the Λ+c→pK−π+ decay and Λ+c baryon polarization measurement in semileptonic beauty hadron decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Leverington, Blake; Li, Peilian; et al. (Physical review, 2023)
An amplitude analysis of Λ+c→pK−π+ decays together with a measurement of the Λ+c polarization vector in semiōleptonic beauty hadron decays is presented. A sample of 400 000 candidates is selected from proton-proton collisions recorded by the LHCb detector at a center-of-mass energy of 13 TeV. An amplitude model is developed and the resonance fractions as well as two- and three-body decay parameters are reported. The mass and width of the Λ(2000) state are also determined. A significant Λ+c polarization is found. A large sensitivity of the Λ+c→pK−π+ decay to the polarization is seen, making the amplitude model suitable for Λ+c polarization measurements in other systems.
*LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und 997 Personen]
Im Titel sind die Zeichen + und - hochgestellt und der Buchstabe c tiefgestellt
Gesehen am 13.02.2024